Vibration response analysis of free-spanning pipeline based on inner pipe excitation signal - Hang Zhang; Na Lu; Can Cui; Shuqiang Du (Advances in Mechanical Engineering, 2018)
Pipeline is important for gas transportation. Free span of buried pipeline may cause safety problem as a result of decreasing the load-carrying capacity of the pipeline. A method for detecting the free span of buried pipelines based on the inner pipe excitation signal was proposed. Vibration characteristics analysis of the pipe and its surrounding coupling system were discussed by means of the finite element method. A three-dimensional pipe model containing a free-spanning segment with a certain length was established. Transient dynamic response analysis was adopted. Frequency response function plots were generated to analyze the results of simulation. The effects of soil type, the length of the free-spanning segment, and the excitation signal on detection were studied. The results show that (1) the obvious change of the first natural frequency of the pipe with different surroundings can be used to detect the free-spanning segment of pipeline; (2) the harder the soil medium is, the higher the first natural frequency of the pipe and soil surrounding system will be; (3) the longer the length of the free-spanning segment is, the lower the first natural frequency will be.